One Time and Seasonal Irrigation Rates of Corn in Condition of Saline Soils - Ch.V.Toshpulatov; B.B.Tukhtashev; B.T.Mavlonov (Zien Journals, 2023)
Non-compliance with sorghum irrigation norms remains an urgent issue for its cultivation in conditions of medium salinity soils. In order to obtain green mass in sorghum in medium saline sierozemmeadow soils of Syrdarya region, it is desirable to water 4 times at the rate of 600-950 m3 /ha in each irrigation, keeping 70-80-70% compared to LFWC before watering the plant during the growing season is appropriate. When irrigating corn in this manner, 665-692 m3 /ha of water is saved from each hectare of corn field. This is an important factor in saving water, and is the highest measure to protect against secondary salinity in the conditions of saline soils.
Keywords: agricultural crops; irrigation; saline soils